Pentakosta Menurut Injil Yohanes: Studi Eksegetis Yohanes 20:22-23 - Eklepinus Jefry Sopacuaperu (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2020)
This article aims to elaborate on the disciple's experience of Pentecost according to the gospel of John. On the one hand, the study's purpose is to introduce the readers to the occurrence of Pentecost that took place during Jesus' appearance to the disciples as narrated in the gospel of John. On the other hand, the study intends to awaken readers' awareness to explore the contrasts and delve into the uniqueness between the narratives of Pentacost as accounted in Acts 2:1-13 and John 20:22-23. Therefore, this article is an exegetical study that focuses on the study of the text and its intercorrelation with the context of the text. Furthermore, it is a great hope that this writing will open a space for theological discourse.